2020
DOI: 10.1101/2020.01.31.928523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two dominant brain states reflect optimal and suboptimal attention

Abstract: 2Attention is not constant but fluctuates from moment to moment. Previous studies 1 3 dichotomized these fluctuations into optimal and suboptimal states based on behavioral 1 4 performance and investigated the difference in brain activity between these states. Although 1 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…Historically, the majority of research on sustained attention has studied attention to external stimuli during psychological tasks requiring top-down attentional control and cognitive effort. 5,[60][61][62] Complementary work has described states of attention associated with less subjective effort, such as flow states of complete absorption in an activity, 8 in-the-zone moments of optimal task performance, [63][64][65][66] and soft fascination to natural environments or aesthetic pieces of art. 67,68 Recent work has also characterized stimulus-independent internal attention and mind wandering.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the majority of research on sustained attention has studied attention to external stimuli during psychological tasks requiring top-down attentional control and cognitive effort. 5,[60][61][62] Complementary work has described states of attention associated with less subjective effort, such as flow states of complete absorption in an activity, 8 in-the-zone moments of optimal task performance, [63][64][65][66] and soft fascination to natural environments or aesthetic pieces of art. 67,68 Recent work has also characterized stimulus-independent internal attention and mind wandering.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to expectations, we did not observe any increase in DMN activity during mind wandering. Although this finding seems counterintuitive, previous studies have reported a similar association between the recruitment of DMN regions and optimized behavior ( "in-the-zone "), whereas suboptimal behavioral performance ( "out-the-zone ") was instead associated with DAN activation ( Esterman et al, 2014 ;Kucyi et al, 2017 ;Yamashita et al, 2020 ). Although speculative, together these findings may point to DMN activity during task-focused attention as representing a weaker engagement in goal-directed behavior or attentional stability needed to accurately perform the task.…”
Section: Discussionmentioning
confidence: 72%
“…In conclusion, state IV was a strong state with the highest network integration and segregation; state III was a sparse state with the least segregation ability (Wang et al, 2020). The degree of network integration and segregation of states I and II were between states III and IV; hence, we refer to states I and II as suboptimal states based on the topological properties, showing the network's redundancy (Yamashita et al, 2021).…”
Section: Discussionmentioning
confidence: 88%